Microbiological and Sensorial Quality of Beef Meat (Longissimus dorsi) Marinated with Cinnamon Extract and Stored at Various Temperatures - Zawani C.J. (2023)
Meat spoilage caused by temperature abuse is a major problem for producers, retailers, and consumers that can generate large economic losses to industries. Microbial growth of Pseudomonas spp. is the main source of spoilage during storage. Cinnamon has antimicrobial properties that may potentially be used to reduce the spoilage caused by Pseudomonas. The objectives of this study were to determine the inhibitory effect of cinnamon extract (CE) against Pseudomonas aeruginosa (ATCC 27853) and evaluate the treatment of CE on meat quality during different storage temperatures (5 °C, 10 °C, 15 °C, and 25 °C). The anti-Pseudomonas result showed that 100% (w/v) CE concentration produced a 13.50 mm zone of inhibition in a disc diffusion assay. The minimum inhibitor concentration (MIC) of CE was noted at 25% (v/v), whereas the minimum bactericidal concentration (MBC) value was observed at 50% (v/v) concentration of CE. The time-kill showed the growth of P. aeruginosa decreased from 7.64 to 5.39 log CFU/mL at MIC concentration. Total phenolic content and IC50 value of the cinnamon extract was expressed as 6.72 ± 0.87 mg GAE/g extract and 0.15 mg/mL, respectively. When the meat was marinated with 50% (v/v) CE and stored at various temperatures, the total viable count (TVC) and growth of Pseudomonas spp. were lowered as compared to the control sample. However, the reduction in microbial count in all samples was influenced by the storage temperature, where the lowered microbial count was noted in the sample treated with CE and stored at 5 and 10 °C for 48 h. The pH of meat treated with or without CE ranged from pH 5.74 to 6.48. The sensory attributes of colour, texture, and overall acceptability have a significant difference, except for odour, between marinated meat and control. The results indicate that the use of cinnamon extract as the marination agent for meat could reduce the growth of Pseudomonas spp. and therefore assist in extending the shelf life of meat at 5 and 10 °C storage temperatures.